2012
DOI: 10.1111/aogs.12025
|View full text |Cite
|
Sign up to set email alerts
|

The appropriate cone depth to avoid endocervical margin involvement is dependent on age and disease severity

Abstract: Age, disease severity and cone depth are predictive factors for endocervical margin involvement. In women of reproductive age, the appropriate cone depth to avoid endocervical margin involvement can be changed depending on age and disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 21 publications
2
33
2
Order By: Relevance
“…In 2011, the IFCPC reported the definition of cone length as the distance from the distal or external margin to the proximal or internal margin of the excised specimen [ 13 ]. We found several studies which analyzed optimal cone length to avoid positive cone margin, but most of them analyzed cone depth rather than cone length [ 15 16 ]. Milinovic et al [ 17 ] reported the appropriate length of conizaiton as 18 mm in multiparous and 15 mm in nulliparous patients to secure a negative margin status, and that was the only study which analyzed appropriate cone length for CIN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, the IFCPC reported the definition of cone length as the distance from the distal or external margin to the proximal or internal margin of the excised specimen [ 13 ]. We found several studies which analyzed optimal cone length to avoid positive cone margin, but most of them analyzed cone depth rather than cone length [ 15 16 ]. Milinovic et al [ 17 ] reported the appropriate length of conizaiton as 18 mm in multiparous and 15 mm in nulliparous patients to secure a negative margin status, and that was the only study which analyzed appropriate cone length for CIN.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, we design conization according to colposcopic findings such as type of transformation zone (TZ) [ 13 14 ] and position of the lesion. Several studies reported on appropriate cone depth [ 15 16 ], but we found only one small study which reported appropriate cone length to avoid positive cone margin. This study examined the risk factors of positive cone margin and identified the appropriate cone length necessary to avoid positive cone margin.…”
Section: Introductionmentioning
confidence: 88%
“…In addition to the technique itself, margin involvement was found to be associated with the patient's age and menopause status in the present study. Some studies have confirmed the relationship between age and endocervical margin but not the relationship between age and ectosurgical margin[ 18 , 19 ]. Bae et al reported that the risk of endocervical margin involvement increases with the age (the odd ratios were 1.59 for 40– to 59-year-old patients and 4.16 in patients over 60 years compared to patients younger than 40 years) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have confirmed the relationship between age and endocervical margin but not the relationship between age and ectosurgical margin[ 18 , 19 ]. Bae et al reported that the risk of endocervical margin involvement increases with the age (the odd ratios were 1.59 for 40– to 59-year-old patients and 4.16 in patients over 60 years compared to patients younger than 40 years) [ 18 ]. This finding might be due to the migration of the transformation zone to the cervical canal with the age and following menopause, which leads to difficulties in removing the intact transformation zone in elderly and postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…A pre-surgical variable that was found to be associated with endocervical cone margin status in this study was age. Many previous studies in the literature have reported increasing age as a risk factor for positive surgical cone margins [11,13,19,20]. This association is mainly due to the more frequent presence of a type 3 transformation zone in this population.…”
Section: Variablesmentioning
confidence: 74%